(untitled) (Historia, 2021)
In the light of student protests in 2015 and 2016 relating to the #RhodesMustFall and #FeesMustFall movements, the significance of the historical discourse has been side- lined. This concept paper discusses the role of digital technologies as platforms to capture and disseminate oral histories, audio-visual sources, historical writings and indigenous knowledge in order to tackle environmental concerns. In South Africa, there is a moral responsibility to encourage previously ignored communities and individuals to collect and share their experiences and knowledge, particularly where this knowledge may be valuable in tackling contemporary challenges. Through better utilisation of oral histories, oral traditions, audio-visual sources, historical writings and indigenous knowledge – as well as better access facilitated by means of digital technologies – the sustainability of historical discourse, the asset-worth of these sources and the viability of the archival institutions and the similar heritage entities housing these items, could be assured. Historians and archivists need to engage actively in highlighting collections, demonstrating their relevance to contemporary challenges and interacting with society at large to ensure that the histories recorded, captured and disseminated represent all communities. Better dissemination of these information sources could provide more effective solutions to deal with contemporary environmental concerns, such as climate change.